Maternal vitamin D status and risk of childhood overweight at 5 years of age in two Nordic cohort studies - Amberntsson, Anna; Bärebring, Linnea; Winkvist, Anna; Lissner, Lauren; Meltzer, Helle Margrete; Brantsæter, Anne Lise; Papadopoulou, Eleni; Augustin, Hanna (Frontiers in Nutrition, 2023)
Introduction: Maternal vitamin D status during pregnancy has been suggested to have a role in childhood adiposity development, but results are conflicting. Our aims were to investigate [1] the relationships between maternal 25-hydroxyvitamin D (25OHD) during pregnancy and the child's body mass index (BMI) and risk for overweight at 5 years of age, and [2] maternal pre-pregnancy BMI as effect modifier for these associations. Methods: Data sources included a subsample from the Norwegian Mother, Father and Child Cohort Study (MoBa sub-cohort; N=2,744) and the Swedish GraviD cohort study (N=891). Maternal 25OHD was analyzed in gestational week 18 in the MoBa sub-cohort and week 10 in the GraviD cohort. In the MoBa sub-cohort, parents reported their child's documented measures of weight and length or height from the health card at routine check-up. In the GraviD cohort, this information was collected directly from medical records. Childhood overweight (including obesity) was identified using the International Obesity Task Force cut-offs. Linear and logistic regression models were used to investigate the association between maternal 25OHD and child's BMI and risk of overweight at 5 years of age in each cohort separately, and in a pooled dataset. Results: In the pooled analysis, maternal 25OHD <30 nmol/L was associated with lower BMI in children at 5 years of age, but not with risk of overweight. Interaction analysis showed that the association was predominant among children of mothers with pre-pregnancy BMI ≥25 kg/m 2 . Conclusion: Low maternal vitamin D status, particularly in mothers with overweight or obesity, predicted lower BMI in their five-year-old children. However, there was no evidence of an effect on overweight in these children.